LANGUAGE FUNCTIONS IN THE BASARANG RITUAL: A CULTURAL-LINGUISTIC STUDY OF MINANGKABAU ORAL TRADITION - Aurlani, Febry; Idaman, Akbar (Universitas Islam Sumatera Utara (UISU), 2025)
Language serves as a vital medium in oral traditions—not only for communication but also as a vehicle for transmitting values and reinforcing collective identity. The Basarang ritual in Nagari Kasang, Minangkabau, is a traditional ceremony performed to commemorate the birth of kembar sumbang (twins of opposite sex) and to restore social and cultural harmony within the community. Despite its cultural richness, linguistic studies on Basarang remain scarce compared to other Minangkabau traditions. This research investigates the functions of language in the Basarang ritual through Roman Jakobson’s (1960) model of language functions, employing a qualitative framework and an ethnography of communication approach (Spradley, 1997; Duranti, 1997). Data were collected through observation, interviews, and documentation of ritual utterances, mamang (chants), pantun (poetic verses), and prayers. The analysis categorizes linguistic expressions according to Jakobson’s six language functions—referential, emotive, conative, phatic, metalingual, and poetic—allowing systematic interpretation of their realization in ritual discourse. Findings reveal that language in Basarang functions not merely as a communicative tool but as a symbolic medium that legitimizes customary law, nurtures social solidarity, and transmits moral and cultural values. This study extends Jakobson’s framework by embedding it within the ethnolinguistic context of Minangkabau ritual discourse, offering contributions to both linguistic theory and cultural preservation.